2015
DOI: 10.1136/bjsports-2015-094927
|View full text |Cite
|
Sign up to set email alerts
|

The dose–response effect of physical activity on cancer mortality: findings from 71 prospective cohort studies

Abstract: BackgroundThe WHO recommends moderate physical activity to combat the increasing risk of death from chronic diseases. We conducted a meta-analysis to assess the association between physical activity and cancer mortality and the WHO recommendations to reduce the latter.MethodsMEDLINE and EMBASE were searched up until May 2014 for cohort studies examining physical activity and cancer mortality in the general population and cancer survivors. Combined HRs were estimated using fixed-effect or random-effect meta-ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
128
2
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 215 publications
(143 citation statements)
references
References 43 publications
9
128
2
4
Order By: Relevance
“…The AICR/WCRF reports that there is convincing evidence that physical activity reduces colorectal cancer risk, and there is probable evidence that it reduces postmenopausal breast and endometrial cancers. 34,36,65 A recent meta-analysis 80 that included 71 cohort studies found that individuals who participated in the most physical activity had an HR of 0.83 (95% CI 0.79 to 0.87) and 0.78 (95% CI 0.74 to 0.84) for cancer mortality in both the general population and among cancer survivors, respectively.…”
Section: Modifiable Cvd Risk Factors and Their Cancer Riskmentioning
confidence: 99%
“…The AICR/WCRF reports that there is convincing evidence that physical activity reduces colorectal cancer risk, and there is probable evidence that it reduces postmenopausal breast and endometrial cancers. 34,36,65 A recent meta-analysis 80 that included 71 cohort studies found that individuals who participated in the most physical activity had an HR of 0.83 (95% CI 0.79 to 0.87) and 0.78 (95% CI 0.74 to 0.84) for cancer mortality in both the general population and among cancer survivors, respectively.…”
Section: Modifiable Cvd Risk Factors and Their Cancer Riskmentioning
confidence: 99%
“…Exercise has also been shown to reduce all-cause mortality as well as both cancer [21] and cardiovascular-related mortality [22]. Importantly, while exercise can increase aerobic fitness as well as modify traditional CVD risk factors [23], exercise may also help protect the heart from the associated cardiotoxic effects of AC-based therapy [24].…”
Section: Introductionmentioning
confidence: 99%
“…In adults, it appears that the most effective strategies for increasing physical activity levels after treatment are individualized programs that are initiated under supervision and are later adopted into life-style behaviors in an unsupervised setting [38,51]. It is not clear whether this is an ideal strategy for childhood cancer patients, but it appears that most current pediatric cancer exercise programs implement this approach [39,40].…”
Section: Introductionmentioning
confidence: 99%